Inhibition of lymphatic proliferation by the selective VEGFR-3 inhibitor SAR131675 ameliorates diabetic nephropathy in db/db mice - Hwang, Seun Deuk (Cell Death Dis, 2019)
Recent studies have demonstrated that chronic inflammation-induced lymphangiogenesis plays a crucial role in the progression of various renal diseases, including diabetic nephropathy. SAR131675 is a selective vascular endothelial cell growth factor receptor-3 (VEGFR-3)-tyrosine kinase inhibitor that acts as a ligand for VEGF-C and VEGF-D to inhibit lymphangiogenesis. In this study, we evaluated the effect of SAR131675 on renal lymphangiogenesis in a mouse model of type 2 diabetes. Male C57BLKS/J db/m and db/db mice were fed either a regular chow diet or a diet containing SAR131675 for 12 weeks from 8 weeks of age. In addition, we studied palmitate-induced lymphangiogenesis in human kidney-2 (HK2) cells and RAW264.7 monocytes/macrophages, which play a major role in lymphangiogenesis in the kidneys. SAR131475 ameliorated dyslipidemia, albuminuria, and lipid accumulation in the kidneys of db/db mice, with no significant changes in glucose and creatinine levels and body weight. Diabetes-induced systemic inflammation as evidenced by increased systemic monocyte chemoattractant protein-1 and tumor necrosis factor-α level was decreased by SAR131475. SAR131475 ameliorated the accumulation of triglycerides and free fatty acids and reduced inflammation in relation to decreased chemokine expression and pro-inflammatory M1 macrophage infiltration in the kidneys. Downregulation of VEGF-C and VEGFR-3 by SAR131475 inhibited lymphatic growth as demonstrated by decreased expression of LYVE-1 and podoplanin that was further accompanied by reduced tubulointerstitial fibrosis, and inflammation in relation to improvement in oxidative stress and apoptosis. Treatment with SAR131475 improved palmitate-induced increase in the expression of VEGF-C, VEGFR-3, and LYVE-1, along with improvement in cytosolic and mitochondrial oxidative stress in RAW264.7 and HK2 cells. Moreover, the enhanced expression of M1 phenotypes in RAW264.7 cells under palmitate stress was reduced by SAR131475 treatment. The results suggest that modulation of lymphatic proliferation in the kidneys is a new treatment approach for type 2 diabetic nephropathy and that SAR131675 is a promising therapy to ameliorate renal damage by reducing lipotoxicity-induced lymphangiogenesis.